Implementasi Program Smart Card Blu-E dalam Pelayanan Kir di Kota Pekanbaru - Dicky Rifawanda; Mayarni Mayarni (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The BLU-E smart card is one of the programs developed by the Indonesian Ministry of Transportation, in this case it aims to facilitate the distribution and issuance of proof of passing periodic motor vehicle tests so that it is fast, efficient, integrated, transparent and reduces data leaks. This research aims to find out and understand how the BLU-e Smart Card is implemented in KIR Services in Pekanbaru City and the supporting and inhibiting factors in the implementation of BLU-e Smart Cards in KIR Services in Pekanbaru City. The theory used in this research is aspects of program implementation according to Jones in Dedi et al. (2017) which is divided into three main indicators, including organizational aspects, interpretation aspects, and implementation or application aspects. The research method used is a qualitative approach with descriptive methods. The data collection techniques in this research are observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results obtained in this research are that the implementation of the BLU-e Smart Card in KIR Services in Pekanbaru City is quite good. Where the supporting factors in using the BLU-e smart card at the UPT-PKB of the Pekanbaru City Transportation Service are ease of access, minimal fraud, and transparency of the budget used. The inhibiting factor in using BLU-e smart cards at the UPT-PKB of the Pekanbaru City Transportation Service is that there are still many people who do not understand the use of BLU-e Smart cards and there is a lack of public awareness of the benefits of vehicle fitness testing.